A study into the incidence of claims and disputes in the Singapore construction industry - Heng, Kim Huat. (2009)
This dissertation reviewed the construction claims profile in the Singapore construction industry between 1985 to 1994. This was done through a postal survey to 1006 randomly selected respondents comprising contractors, developers and consultants. Out of 110 returns, 68 respondents which have been involved with claims were analysed in detail.